2023
DOI: 10.3389/fimmu.2023.1140755
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the prediction of all-cause mortality in patients with sepsis-associated acute kidney injury during hospitalization

Abstract: BackgroundSepsis-associated acute kidney injury (S-AKI) is considered to be associated with high morbidity and mortality, a commonly accepted model to predict mortality is urged consequently. This study used a machine learning model to identify vital variables associated with mortality in S-AKI patients in the hospital and predict the risk of death in the hospital. We hope that this model can help identify high-risk patients early and reasonably allocate medical resources in the intensive care unit (ICU).Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…In addition, the random forest algorithm was proved to perform better than logistic regression models using SAPS II, APACHE IV, and SOFA. Zhou et al [ 13 ] also developed multiple machine learning models for mortality prediction of S-AKI patients using the MIMIC-IV dataset, and the CatBoost model was reported to perform the best. However, only model discriminability was assessed during performance evaluation, and no sample size calculation was performed to justify the sufficiency of the training sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the random forest algorithm was proved to perform better than logistic regression models using SAPS II, APACHE IV, and SOFA. Zhou et al [ 13 ] also developed multiple machine learning models for mortality prediction of S-AKI patients using the MIMIC-IV dataset, and the CatBoost model was reported to perform the best. However, only model discriminability was assessed during performance evaluation, and no sample size calculation was performed to justify the sufficiency of the training sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Some models were developed using the AKI dataset for predicting the risk of death in SAKI patients, which is subject to bias in cohort selection. Furthermore, many studies did not calculate the sample size before constructing the final models [ [10] , [11] , [12] , [13] ]. This issue easily leads to ineffectiveness of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring these 2 parameters in the early stages of SIC patients can aid in assessing renal function, identifying sepsis-related acute kidney injury, and predicting disease progression and prognosis. [ 31 ] As an essential physiological parameter in the human body, SpO 2 serves to assess the circulatory system functionality and stands as a crucial monitoring indicator in early resuscitation protocols. [ 32 ] Lara Hessels et al’s study revealed a close association between potassium disturbances and in-hospital mortality, which persisted even after adjusting for disease severity and acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) are rapidly emerging as transformative tools for diagnosing and managing AKI patients [12][13][14][15][16][17][18][19][20][21]. Compared to traditional methods, ML algorithms can reveal patterns beyond human discernment and enhance SA-AKI prediction accuracy by analyzing vast datasets [22][23][24][25][26][27]. Furthermore, ML enables earlier SA-AKI detection than traditional approaches, allowing timely, appropriate intervention and improved outcomes [12][13][14][15][16][17][18][19][20]24,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary research increasingly explores AI/ML's capabilities to advance precision medicine and tailored SA-AKI care. The integration of these technologies promises to usher in a new era of early detection and optimized therapeutic interventions for SA-AKI [22][23][24][25][26][27]. Several stateof-the-art studies and initiatives are currently underway, highlighting the adoption of these technologies in various clinical settings, each aiming to address the profound challenges posed by SA-AKI with a degree of sophistication previously unattainable [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%